Polymer electrolyte membrane and preparation method thereof

By using the combination of esterification reaction and organic lithium salt in the polymer electrolyte membrane, a stable lithium ion channel is formed, which solves the problems of water loss and poor liquid absorption in traditional membranes at high temperatures, and achieves rapid lithium ion transmission and battery Performance improvement.

CN119253051AActive Publication Date: 2025-01-03HUNAN YANKE NEW ENERGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411469770.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-03
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

Traditional polymer electrolyte membranes are prone to water loss at high temperatures, resulting in hindered lithium ion transmission and degradation of battery performance. The membrane's absorption effect on electrolyte is poor, making it prone to electrostatic breakdown, resulting in deterioration of battery performance.

Method used

The esterification reaction is carried out using heterocyclic compounds and diols, and linear polyether compounds and organolithium salts are added to form a substrate through thermal reaction and drying, which enhances the mechanical properties and electrical conductivity of the film, and ensures the stability of the film using vacuum drying technology.

Benefits of technology

It improves the lithium ion transmission efficiency, enhances the liquid absorption capacity and high temperature stability of the film, and maintains the ionic conductivity and electrochemical properties of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253051A_ABST
    Figure CN119253051A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrolyte membranes, and particularly relates to a polymer electrolyte membrane and a preparation method thereof. The method comprises the following steps: 1) uniformly mixing a heterocyclic compound and dihydric alcohol A, carrying out a thermal reaction, sequentially adding dihydric alcohol B and a catalyst, uniformly mixing, carrying out an esterification reaction, and cooling to obtain a base material; and 2) mixing a linear polyether compound and an organic lithium salt into the substrate in an inert gas atmosphere, adding a dispersing agent, uniformly mixing, injecting into a thin film mold, standing for reaction, and drying to obtain the polymer electrolyte membrane. The polymer electrolyte membrane prepared by the invention is short in lithium ion transportation path, high in transmission efficiency and good in ionic conductivity, meanwhile, the surface of the polymer electrolyte membrane is provided with an array structure, the polymer electrolyte membrane can be quickly wetted, excellent liquid absorption rate is shown, and good dimensional stability and performance stability are kept under high-temperature and pressure conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrolyte membranes, and in particular relates to a polymer electrolyte membrane and a preparation method thereof. Background Art

[0002] With the development of science and technology, lithium batteries are gradually widely used in various fields. Lithium batteries include positive electrodes, negative electrodes, electrolytes, etc. Among them, liquid electrolytes are widely used because of their excellent ionic conductivity. Since liquid electrolytes are prone to leakage, polymer electrolyte membranes are often prepared to separate the two electrodes.

[0003] It is often impossible to form continuous reduced lithium substances on traditional polyether and polycarbonate-based polymer electrolyte membranes, which will cause significant degradation of battery performance. In addition, commercially available polymer electrolyte membranes have the following main problems: 1) The membrane pore size is too large, which makes it easy for the two electrodes to directly contact and short-circuit, but the membrane with too small pore size leads to a long lithium ion transport path, which makes it difficult for lithium ions to diffuse; 2) The electrolyte has poor wettability on the membrane, and the membrane has poor absorption effect on the electrolyte. Electrostatic breakdown occurs due to lithium dendrites and liquid dry areas in the membrane, which significantly affects the performance of the battery; 3) At higher temperatures, the mobility of the polymer chain is enhanced, and the structural bonding points are destroyed, resulting in poor dimensional stability. The membrane shrinks and causes the two electrodes to directly contact and fail. Furthermore, under continuous high temperatures, the polymer electrolyte membrane is prone to water loss, which destroys the hydrogen bond network in the membrane, reduces the proton transmission path, and causes a decrease in proton conductivity.

[0004] Most importantly, membrane shrinkage will hinder lithium ion transmission, causing changes in resistance, resulting in poor ion conductivity of the battery, further reduction in active electrode area, and reduced battery charge and discharge efficiency. Continuous high temperature environment will cause irreversible damage to the electrolyte membrane, and membrane shrinkage will form stress and cause electrons to be squeezed, resulting in increased battery resistance and deteriorated performance.

[0005] Therefore, it is necessary to develop a polymer electrolyte membrane that can solve the above problems. Summary of the invention

[0006] Based on the above content, in order to solve the problems that the membrane is easily damaged by lithium dendrites, the membrane has poor absorption effect on electrolyte, and the membrane has poor stability, the present invention proposes a polymer electrolyte membrane and a preparation method thereof.

[0007] The objects of the present invention are: 1. Ensure that lithium ions can pass through the polymer electrolyte membrane in large quantities; 2. Improve the wettability of polymer electrolyte membrane and enhance its liquid absorption capacity; 3. Enhanced polymer electrolyte membrane maintains dimensional stability at high temperatures.

[0008] To achieve the above objectives, the present invention adopts the following technical solutions.

[0009] A method for preparing a polymer electrolyte membrane, The method comprises: 1) Mix the heterocyclic compound and diol A evenly, perform a thermal reaction, add diol B and a catalyst in sequence, mix evenly, perform an esterification reaction, and cool to obtain a substrate; 2) In an inert gas atmosphere, a linear polyether compound and an organic lithium salt are mixed into a substrate, a dispersant is added and mixed evenly, the mixture is injected into a film mold and allowed to react, and a polymer electrolyte membrane is obtained after drying.

[0010] As a preference, Step 1) the heterocyclic compound is 2-methyl-1,2-oxophosphine-5-one 2-oxide; The 2-methyl-1,2-oxaphosphol-5-one 2-oxide is 2-Methyl-1,2-oxaphospholan-5-one2-oxide, and its CAS number is 15171-48-9; Step 1) The diol A is ethylene glycol, and its usage is 0.5-0.6 mL / mL heterocyclic compound.

[0011] As a preference, Step 1) The thermal reaction process is: In an inert gas atmosphere, heat to 120-140 °C and keep the temperature constant for 3.5-4.5 h.

[0012] As a preference, Step 1) the diol B is 1,4-butanediol, and its usage is 0.81-0.94 mL / mL heterocyclic compound; Step 1) The catalyst is a molecular sieve with a pore size of less than or equal to 0.5 nm, and the amount used is 0.02-0.06 g / mL of heterocyclic compound.

[0013] As a preference, Step 1) The esterification reaction process is: In an inert gas atmosphere, heat to 150-170 °C and keep the temperature constant for 5.5-6.5 h.

[0014] As a preference, Step 2) the linear polyether compound is polyethylene oxide, and 3 to 3.5 mL of the linear polyether compound is added per gram of substrate; Step 2) the organic lithium salt is a 0.5-0.8 mol / L n-butyl lithium solution, and 0.1-0.3 mL of the organic lithium salt is added per gram of substrate; The n-butyl lithium solutions referred to in the present invention are all commercially available n-butyl lithium n-pentane solutions; Step 2) The dispersant is dichloromethane, and 100 to 150 mL of the dispersant is added per gram of substrate.

[0015] As a preference, Step 2) The drying is carried out by constant temperature vacuum drying; Step 2) The drying process is controlled at a temperature of ≤25°C.

[0016] As a preference, Step 2) The drying process is controlled at a temperature of 15-25°C.

[0017] A polymer electrolyte membrane.

[0018] During the transmission of lithium ions, lithium ions form a pathway through a potential barrier. The polyethylene oxide skeleton inevitably shrinks due to high temperature, causing changes in the pathway path and a decrease in lithium ion conductivity. The mobility of the polyethylene oxide molecular chain is enhanced, and cracks are easily generated. The penetration of the cracks will cause direct contact between the two electrodes, leading to battery deterioration. At the same time, the shrinkage stress causes the electrons to be squeezed, causing the battery resistance to increase. To solve this problem, the technical solution of the present invention first prepares a substrate with an asymmetric structure of adjacent carbon atoms, and uses ethylene glycol and 1,4-butanediol for diol treatment. The ethylene glycol chain is first broken, which is a prerequisite for the introduction of an alcohol ester structure into the material, and then catalyzed esterification is formed to form an alcohol ester compound.

[0019] During the preparation process, temperature can significantly affect lithium ion coordination clusters and porosity, thereby affecting lithium ion transmission. High temperature helps to increase the size of lithium ion coordination clusters and reduce penetrating holes and lattice defects. However, too high a temperature will cause the material resistance to increase and the piezoresistance coefficient to increase. Therefore, the preparation temperature should be controlled to retain appropriate lattice defects. After diol treatment, 1,4-butanediol segments are introduced into the main chain of the heterocyclic compound, which effectively increases the viscosity of the solution. After molding, it is beneficial to enhance the mechanical properties of the material to avoid shrinkage and internal structure collapse of the film material during the subsequent molding process, resulting in a decrease in its electrochemical performance. The phosphorus-oxygen single bond and phosphorus-oxygen double bond in the alcohol ester compound are converted by heat, which can inhibit the release of hydrogen radicals and oxygen radicals during the thermal decomposition process, improve the piezoresistive effect of the polymer electrolyte membrane, and enhance the high-temperature dimensional stability of the material.

[0020] There are multiple -CH2CH2O- segments in the structure of polyethylene oxide, and the movement of the segments can promote the movement of lithium ions. However, due to the regular lithium ion transport channel and high crystallinity, lithium ions are easy to migrate in the amorphous region, resulting in low ionic conductivity of the polymer electrolyte membrane. In the technical solution of the present invention, the hydrogen bonds between the hydroxyl groups of the substrate and the polymer and the asymmetric active hydroxyl structure in the substrate are conducive to the construction of lithium ion transport channels, which are conducive to overcoming the problem of lithium ion migration in the amorphous region. The synergistic effect of multiple bonding promotes the rapid migration of lithium ions. At the same time, hydrogen bonds weaken the coordination of lithium ions and oxygen, and enhance the interface stability. This structure reduces the density while not significantly reducing the mechanical properties of the membrane, avoiding cracks in the polymer skeleton due to external stress stimulation.

[0021] On this basis, the present invention further adds and uses a specific organic lithium salt. The organic lithium salt used is a strong base and an organic reagent with strong nucleophilic ability, which can react with the formed alcohol ester compound and polyethylene oxide to form and construct and stabilize the lithium ion transport channel. In addition, the introduction of an appropriate amount of lithium ions in the preparation process of the electrolyte membrane can generally improve the conductivity of the electrolyte membrane to a certain extent, improve the mechanical properties of the electrolyte membrane, and enhance the electrochemical stability of the electrolyte membrane. However, for the technical solution of the present invention, a certain degree of controllable assembly is actually achieved. In the drying process of step 2), due to the gradual volatilization of dichloromethane, the hydrogen bonds between the substrate hydroxyl group and the polymer and the asymmetric active hydroxyl structure in the substrate will be affected, and may shrink and collapse. In particular, for the hydrogen bonds between the substrate hydroxyl group and the polymer, it will cause the rearrangement of the substrate and the polymer. In this case, the present invention can form a bond or connect and fix with the alcohol ester compound substrate and polyethylene oxide to a certain extent by introducing a strong base and a strong nucleophilic ability organic lithium salt. At the same time, the introduced lithium ions are also conducive to avoiding hydrogen bond rearrangement, thereby effectively maintaining the formed lithium ion channel, ensuring that the electrolyte membrane of the present invention has good stability and electrochemical properties. However, organic lithium salts with strong base and strong nucleophilicity are usually very active. In terms of selection, the present invention has only found that n-butyl lithium has a relatively good preparation effect, but n-butyl lithium is still relatively active, and common drying processes such as heat drying and freeze drying will generally cause irreversible effects on film material forming. For example, heat drying may cause the remaining n-butyl lithium to burn during the static curing molding process, while freeze drying will have a more significant impact on the hydrogen bond between the substrate hydroxyl group and the polymer, and the asymmetric active hydroxyl structure in the substrate, and at the same time cause the pre-product before complete curing molding to produce physical shrinkage, resulting in a decrease in thickness but also a simultaneous decrease in ion conductivity, because the lithium ion channel collapses and decreases, and the present invention specifically uses vacuum drying under room temperature conditions, and removes the solvent under mild conditions to increase the concentration of n-butyl lithium in disguise, thereby activating its reaction activity to a certain extent, achieving the fixation of the channel and enhancing the conductivity of the electrolyte membrane, significantly optimizing the various properties of the electrolyte membrane and ensuring the safety of industrial production and processing.

[0022] Furthermore, the copolymer forms an array structure on the outer surface of the membrane, which increases the contact area between the liquid and the membrane, reduces the mass transfer resistance, and promotes the electrode reaction. The synergistic hydrophilic phosphonic acid group can enhance the material's liquid absorption capacity, can be completely wetted, and promote Li + OH - transmission.

[0023] The material structure prepared by the present invention is special. Different from the product of directly adding monomers with good thermal stability and copolymerizing, the electrolyte membrane of the present invention constructs a stable lithium ion channel by combining organic polymers with organic lithium salts. When subjected to pressure, lithium ions can still migrate in an orderly manner, and there is no obvious relaxation process at the interface, which can significantly improve the piezoresistive effect. The method of increasing the density of the polymer network and reducing the movement of chain segments at high temperatures by chemical or physical cross-linking will cause the migration of lithium ions to be hindered. At the same time, the material chain is long and overlaps with each other, which reduces the material's ability to maintain structural stability at high temperatures. The addition of thermally stable fillers may cause the appearance and expansion of cracks due to stiffness mismatch, resulting in a more serious piezoresistive effect.

[0024] The beneficial effects of the present invention are as follows: (1) The polymer electrolyte membrane prepared by the present invention has a short lithium ion transport path, high transmission efficiency, and exhibits good ion conductivity; (2) The surface of the polymer electrolyte membrane prepared by the present invention has an array structure, can be wetted quickly, and exhibits excellent liquid absorption rate; (3) The polymer electrolyte membrane prepared by the present invention can maintain good dimensional stability and performance stability under high temperature and pressure conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM characterization image of the polymer electrolyte membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with specific embodiments and the accompanying drawings. A person of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by a person of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0027] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0028] Embodiment 1: A method for preparing a polymer electrolyte membrane, the method comprising: 1) Take 10 mL of 2-methyl-1,2-phosphino-5-one 2-oxide and 5 mL of ethylene glycol and mix them evenly. Heat them to 120 °C in a nitrogen atmosphere and keep the temperature constant for 4 h. Then add 8.1 mL of 1,4-butanediol and 0.2 g of molecular sieve with a pore size of 0.4 nm and mix them evenly. Heat them to 150 °C in a nitrogen atmosphere and keep the temperature constant for 6 h. Then cool them to obtain the substrate. 2) In a nitrogen atmosphere, polyethylene oxide was mixed into the substrate, 3 mL of polyethylene oxide was mixed into each gram of substrate, 0.2 mL of 0.5 mol / L n-butyl lithium n-pentane solution was added into each gram of substrate, 100 mL of dichloromethane was added into each gram of substrate and mixed evenly, the mixture was injected into a film mold and allowed to react for 3 h, and then vacuum dried at 20 °C to obtain a polymer electrolyte membrane.

[0029] The polymer electrolyte membrane prepared in this example was characterized by SEM. Figure 1 As shown. Figure 1 It can be clearly seen from the characterization results that the polymer electrolyte membrane prepared by the present invention has a very high porosity and a rich pore structure distributed on the surface, thereby having abundant ion channels and a large liquid absorption space. On the other hand, the pores are hierarchically distributed and have a larger specific surface area, and are distributed with a small amount of flaky nanostructures.

[0030] The polymer electrolyte membrane of this example was tested for performance using the following method.

[0031] 1. Liquid absorption test The polymer electrolyte membrane prepared in this example was immersed in deionized water for 4 h, and the mass difference of the membrane before and after immersion was calculated. Calculate the liquid absorption of the membrane.

[0032] The formula is: .

[0033] 2. Electrochemical performance test A lithium sheet and germanium graphene with the same diameter were used as two electrodes, and assembled into a battery with the electrolyte membrane prepared in this example, and tested using an SC28-CHI660E electrochemical workstation. Cyclic voltammetry tests were performed under the conditions of H2 being introduced into the anode side and N2 being introduced into the cathode side, with a gas flow rate of 1000 mL / min. At 40 °C, the scanning voltage range was set to 0.01-1.5 V, and the scanning speed was 20 mV / s. After multiple scans, the cyclic voltammetry test results were used to detect whether there was a significant voltage shift in the oxidation-reduction process. After 50 cycles at 0.5 C, the battery capacity retention rate was recorded as DCR1. The same test characterization was performed with commercially available all-polymer solid electrolyte membrane A (purchased from Ampcera, PER / PPC@LLZTO composite solid electrolyte) and commercially available polymer all-solid electrolyte membrane B (purchased from NEI Corporation, PEO / PPC / nano TiO2-PMMA composite solid polymer electrolyte membrane), and the battery capacity retention rates were recorded as DCR2 and DCR3, respectively. The characterization results showed that DCR2>DCR3, so the recorded DCR1 and DCR2 were used to calculate the improvement rate of the battery capacity retention rate of the polymer electrolyte membrane prepared in this example compared with the commercially available high-quality polymer solid electrolyte membrane A. The calculation process is as follows: The improvement rate of battery capacity retention rate △DCR=(DCR1-DCR2) / DCR2×100%.

[0034] 3. Ionic conductivity test The ionic conductivity of the polymer electrolyte membrane prepared in this example was characterized and recorded by AC impedance spectroscopy.

[0035] The results are as follows.

[0036]

[0037] According to the results in the table, the polymer electrolyte membrane in this example has excellent liquid absorption effect because the conical array structure on the surface of the material effectively promotes liquid absorption. Because the polymer electrolyte membrane has a tight network structure, the entanglement of the components reduces cracking and separation, and the particles are evenly dispersed during molding to reduce excess stress, so that the material will not have obvious curling, shrinkage and other phenomena at high temperatures. This shows that the polymer electrolyte membrane has strong high-temperature dimensional stability. In addition, after applying dynamic pressure clamping with a pressure of 3 to 30 MPa on both sides of the polymer electrolyte membrane of the present invention, an ionic conductivity characterization test was carried out. When the pressurization started, the ionic conductivity showed a trend of first slightly increasing and then decreasing with the increase of pressure. When the dynamic external pressure reached 22 to 30 MPa, the ionic conductivity tended to be stable, reaching about 2.01 mS·cm -1, still showing excellent ionic conductivity. Since there is no obvious interface in the material of this example, there is no obvious relaxation process of lithium ions near the interface, which is manifested as a small change trend of the piezoresistance coefficient.

[0038] Embodiment 2: A method for preparing a polymer electrolyte membrane, the method comprising: 1) Take 10 mL of 2-methyl-1,2-phosphino-5-one 2-oxide and 5 mL of ethylene glycol and mix them evenly. Heat them to 130 °C in a nitrogen atmosphere and keep the temperature constant for 4 h. Then add 8.1 mL of 1,4-butanediol and 0.2 g of molecular sieve with a pore size of 0.4 nm and mix them evenly. Heat them to 160 °C in a nitrogen atmosphere and keep the temperature constant for 6 h. Then cool them to obtain the substrate. 2) In a nitrogen atmosphere, polyethylene oxide was mixed into the substrate, 3 mL of polyethylene oxide was mixed into each gram of substrate, 0.2 mL of 0.5 mol / L n-butyl lithium n-pentane solution was added into each gram of substrate, 100 mL of dichloromethane was added into each gram of substrate and mixed evenly, the mixture was injected into a film mold and allowed to react for 3 h, and then vacuum dried at 20 °C to obtain a polymer electrolyte membrane.

[0039] The polymer electrolyte membrane of this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0040]

[0041] In this case, the substrate was prepared at a higher temperature, which was conducive to the construction of lithium ion transport channels. The size of the ion coordination clusters increased at the microscopic level, and the growth orientation was consistent, which was conducive to the orderly migration of lithium ions and avoided relaxation at the material interface. The ion conductivity test was also carried out under the dynamic pressure of 3-30 MPa. Due to the reduction of lattice defects in the material, the ion conductivity change rate was smaller, and the ion conductivity remained at about 2.05 mS·cm when it tended to equilibrium. -1 At high temperatures, the shrinkage stress has less impact on the battery, and the ionic conductivity of the assembled battery has almost no change, which is conducive to lithium ion transmission and a high battery capacity retention rate.

[0042] Embodiment 3: A method for preparing a polymer electrolyte membrane, the method comprising: 1) Take 10 mL of 2-methyl-1,2-phosphino-5-one 2-oxide and 5 mL of ethylene glycol and mix them evenly. Heat them to 140 °C under nitrogen atmosphere and keep the temperature constant for 4 h. Then add 8.1 mL of 1,4-butanediol and 0.2 g of molecular sieve with a pore size of 0.4 nm and mix them evenly. Heat them to 170 °C under nitrogen atmosphere and keep the temperature constant for 6 h. Then cool them to obtain the substrate. 2) In a nitrogen atmosphere, polyethylene oxide was mixed into the substrate, 3 mL of polyethylene oxide was mixed into each gram of substrate, 0.2 mL of 0.5 mol / L n-butyl lithium n-pentane solution was added into each gram of substrate, 100 mL of dichloromethane was added into each gram of substrate and mixed evenly, the mixture was injected into a film mold and allowed to react for 3 h, and then vacuum dried at 20 °C to obtain a polymer electrolyte membrane.

[0043] The polymer electrolyte membrane of this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0044]

[0045] Although the ionic conductivity of the material decreased in this case, this is because the higher temperature gradually made the material compact and the porosity decreased. Moreover, due to the decrease in porosity, its liquid absorption rate also decreased significantly.

[0046] Comparative Example 1: A method for preparing a polymer electrolyte membrane, the method comprising: 1) Take 10 mL of 2-methyl-1,2-phosphino-5-one 2-oxide and 5 mL of ethylene glycol and mix them evenly. Heat them to 130 °C in a nitrogen atmosphere and keep the temperature constant for 4 h. Then add 8.1 mL of 1,4-butanediol and 0.2 g of molecular sieve with a pore size of 0.4 nm and mix them evenly. Heat them to 160 °C in a nitrogen atmosphere and keep the temperature constant for 6 h. Then cool them to obtain the substrate. 2) In a nitrogen atmosphere, polyethylene was mixed into the substrate, 3 g of polyethylene was mixed into each gram of substrate, 0.2 mL of 0.5 mol / L n-butyl lithium n-pentane solution was added into each gram of substrate, 100 mL of dichloromethane was added into each gram of substrate and mixed evenly, the mixture was injected into a film mold and allowed to react for 3 h, and then vacuum dried at 20 °C to obtain a polymer electrolyte membrane.

[0047] The polymer electrolyte membrane of this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0048]

[0049] The polymer electrolyte in this example is prepared based on the polyethylene main chain, and the material undergoes a deformation-recovery process after being heated. The thermal shrinkage of this material is serious, which is very likely to cause direct contact between the positive and negative electrodes of the battery, causing a short circuit in the battery. At the same time, although lithium ions have certain difficulties in migrating in amorphous areas, due to the poor charge migration ability and loose structure of non-polar materials, the mobility of lithium ions in the transmission channel is also very low, and the ionic conductivity is low. This causes the battery capacity to decay, making it difficult to meet actual needs.

[0050] Comparative Example 2: A method for preparing a polymer electrolyte membrane, the method comprising: 1) Take 10 mL of 2-methyl-1,2-phosphino-5-one 2-oxide and 5 mL of ethylene glycol and mix them evenly. Heat them to 130 °C in a nitrogen atmosphere and keep the temperature constant for 4 h. Then add 8.1 mL of 1,4-butanediol and 0.2 g of molecular sieve with a pore size of 0.4 nm and mix them evenly. Heat them to 160 °C in a nitrogen atmosphere and keep the temperature constant for 6 h. Then cool them to obtain the substrate. 2) In a nitrogen atmosphere, polystyrene was mixed into the substrate, 3 g of polystyrene was mixed into each gram of substrate, 0.2 mL of 0.5 mol / L n-butyllithium n-pentane solution was added into each gram of substrate, 100 mL of dichloromethane was added into each gram of substrate and mixed evenly, the mixture was injected into a film mold and allowed to react for 3 h, and then vacuum dried at 20 °C to obtain a polymer electrolyte membrane.

[0051] The polymer electrolyte membrane of this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0052]

[0053] In this case, a polymer containing an aromatic structure is used to synthesize a polymer main chain with stronger heat resistance, which significantly improves the stability at high temperatures. However, firstly, the liquid absorption rate of the membrane prepared based on polystyrene decreases. Secondly, the polymer density increases, the stiffness increases, and its skeleton is easily cracked due to the shrinkage stress, making it difficult to maintain structural stability. Moreover, the movement of the chain segments hinders the migration of lithium ions, and the battery capacity decays significantly. Lithium ions have a significant relaxation process at the material interface, and the piezoresistive effect is obvious.

[0054] Comparative Example 3: A method for preparing a polymer electrolyte membrane, the method comprising: 1) Take 10 mL of 2-methyl-1,2-phosphino-5-one 2-oxide and 5 mL of ethylene glycol and mix them evenly. Heat them to 130 °C in a nitrogen atmosphere and keep the temperature constant for 4 h. Then add 8.1 mL of 1,4-butanediol and 0.2 g of molecular sieve with a pore size of 0.4 nm and mix them evenly. Heat them to 160 °C in a nitrogen atmosphere and keep the temperature constant for 6 h. Then cool them to obtain the substrate. 2) In a nitrogen atmosphere, polyethylene oxide was mixed into the substrate, 3 mL of polyethylene oxide and 0.05 g of calcium carbonate were mixed into each gram of substrate, 0.2 mL of 0.5 mol / L n-butyl lithium n-pentane solution was added into each gram of substrate, and 100 mL of dichloromethane was added into each gram of substrate and mixed evenly, and then injected into a film mold and allowed to react for 3 h, and then vacuum dried at 20 °C to obtain a polymer electrolyte membrane.

[0055] The polymer electrolyte membrane of this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0056]

[0057] In this case, a small amount of thermally stable filler was added, and the stability of the battery was good at 40 °C. Moreover, the interaction between the C=O polar bond of the material and calcium carbonate can enhance the absorption of calcium carbonate. However, under pressure conditions, due to the mismatch between the rigidity of calcium carbonate and the molecular chain skeleton, cracks formed and expanded, resulting in a more serious piezoresistive effect, and the ionic conductivity never tended to balance. When the external pressure reached 30 MPa, its ionic conductivity dropped to 1.07, which was a very obvious decline.

[0058] Comparative Example 4: A method for preparing a polymer electrolyte membrane, the method comprising: 1) Take 10 mL of 2-methyl-1,2-phosphino-5-one 2-oxide and 5 mL of ethylene glycol and mix them evenly. Heat them to 130 °C in a nitrogen atmosphere and keep the temperature constant for 4 h. Then add 8.1 mL of 1,4-butanediol and 0.2 g of molecular sieve with a pore size of 0.4 nm and mix them evenly. Heat them to 160 °C in a nitrogen atmosphere and keep the temperature constant for 6 h. Then cool them to obtain the substrate. 2) In a nitrogen atmosphere, polyethylene oxide was mixed into the substrate, 3 mL of polyethylene oxide was mixed into each gram of substrate, 0.2 mL of 0.5 mol / L n-butyl lithium n-pentane solution was added into each gram of substrate, 100 mL of dichloromethane was added into each gram of substrate and mixed evenly, the mixture was injected into a film mold and allowed to react for 3 h, and then freeze-dried at -20 °C to obtain a polymer electrolyte membrane.

[0059] The polymer electrolyte membrane of this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0060]

[0061] In this example, freeze drying was used to achieve the final solidification of the product. In fact, the thickness of the solid product was significantly smaller than that of the products obtained in Examples 1 to 3 under the same mold and material amount. In addition, based on the above characterization results, the performance of the product obtained in this example was far inferior to that of Example 2. This is mainly due to the collapse of the lithium ion channel and the macroscopic shrinkage of the polymer electrolyte membrane during the freeze drying process, which caused damage to the internal microstructure and resulted in a very significant performance degradation. When vacuum drying was performed at 5°C, a significant performance degradation also occurred, mainly in the performance degradation of ionic conductivity, which only maintained about 1.36 mS·cm -1This is mainly because although the organic lithium salt gradually shows reaction activity as the concentration in the solvent system increases during the drying process, too low a temperature will inhibit the reaction and it may even be easily removed during the drying process, resulting in poor actual preparation results.

[0062] Comparative Example 5: A method for preparing a polymer electrolyte membrane, the method comprising: 1) Take 10 mL of 2-methyl-1,2-phosphino-5-one 2-oxide and 5 mL of ethylene glycol and mix them evenly. Heat them to 130 °C in a nitrogen atmosphere and keep the temperature constant for 4 h. Then add 8.1 mL of 1,4-butanediol and 0.2 g of molecular sieve with a pore size of 0.4 nm and mix them evenly. Heat them to 160 °C in a nitrogen atmosphere and keep the temperature constant for 6 h. Then cool them to obtain the substrate. 2) In a nitrogen atmosphere, polyethylene oxide was mixed into the substrate at a rate of 3 mL polyethylene oxide per gram of substrate, and 100 mL dichloromethane was added per gram of substrate and mixed evenly, and then injected into a film mold and allowed to react for 3 h, and then vacuum dried at 20 °C to obtain a polymer electrolyte membrane.

[0063] The polymer electrolyte membrane of this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0064]

[0065] In this example, no organic lithium salt was added during the preparation process, which directly led to a significant decrease in the ionic conductivity of the electrolyte membrane. At the same time, from the changes in liquid absorption rate and △DCR, it is also proved that it has a direct impact on improving the performance and structural stability of the electrolyte membrane. The decrease in liquid absorption rate indicates that during the drying process, the internal space was compressed and reduced due to the failure of hydrogen bonds and structural rearrangement. Although the drying conditions were mild, a significant decrease was inevitably produced. With the shrinkage and collapse of the microstructure, and the loss of the ionic conductivity enhancement effect that the organic lithium salt itself can bring, the ionic conductivity of the electrolyte membrane has also deteriorated significantly.

Claims

1. A method for preparing a polymer electrolyte membrane, characterized in that: The method comprises: 1) Mix the heterocyclic compound and diol A evenly, perform a thermal reaction, add diol B and a catalyst in sequence, mix evenly, perform an esterification reaction, and cool to obtain a substrate; 2) In an inert gas atmosphere, a linear polyether compound and an organic lithium salt are mixed into a substrate, a dispersant is added and mixed evenly, the mixture is injected into a film mold and allowed to react, and a polymer electrolyte membrane is obtained after drying.

2. The method for preparing a polymer electrolyte membrane according to claim 1, characterized in that: Step 1) the heterocyclic compound is 2-methyl-1,2-oxophosphine-5-one 2-oxide; Step 1) The diol A is ethylene glycol, and its usage is 0.5-0.6 mL / mL heterocyclic compound.

3. The method for preparing a polymer electrolyte membrane according to claim 1 or 2, characterized in that: Step 1) The thermal reaction process is: In an inert gas atmosphere, heat to 120-140 °C and keep the temperature constant for 3.5-4.5 h.

4. The method for preparing a polymer electrolyte membrane according to claim 1, characterized in that: Step 1) the diol B is 1,4-butanediol, and its usage is 0.81-0.94 mL / mL heterocyclic compound; Step 1) The catalyst is a molecular sieve with a pore size of less than or equal to 0.5 nm, and the amount used is 0.02-0.06 g / mL of heterocyclic compound.

5. The method for preparing a polymer electrolyte membrane according to claim 1 or 4, characterized in that: Step 1) The esterification reaction process is: In an inert gas atmosphere, heat to 150-170 °C and keep the temperature constant for 5.5-6.5 h.

6. The method for preparing a polymer electrolyte membrane according to claim 1, characterized in that: Step 2) the linear polyether compound is polyethylene oxide, and 3 to 3.5 mL of the linear polyether compound is added per gram of substrate; Step 2) the organic lithium salt is a 0.5-0.8 mol / L n-butyl lithium solution, and 0.1-0.3 mL of the organic lithium salt is added per gram of substrate; Step 2) The dispersant is dichloromethane, and 100 to 150 mL of the dispersant is added per gram of substrate.

7. The method for preparing a polymer electrolyte membrane according to claim 1 or 6, characterized in that: Step 2) The drying is carried out by constant temperature vacuum drying; Step 2) The drying process is controlled at a temperature of ≤25°C.

8. The method for preparing a polymer electrolyte membrane according to claim 7, characterized in that: Step 2) The drying process is controlled at a temperature of 15-25°C.

9. A polymer electrolyte membrane obtained by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of polymer electrolyte

    CN108832175A

  • Flame-retardant polyethylene oxide solid electrolyte membrane

    CN112625283A

  • Intrinsic flame-retardant polyurethane solid electrolyte membrane

    CN112812264A

  • Organic matter for improving battery safety and preparation method and application thereof

    CN117126202A